Environmental Risk, Reputational Risk, and Legal Risk as determinants of Performance of Manufacturing Companies in Nigeria - BANJO, Kudirat Adeola; ADULOJU, Sunday Adekunle; Ajemunigbohun, Sunday Stephen (Annals of Spiru Haret University. Economic Series, 2022)
Most manufacturing firms focus on how to improve their effectiveness and pay less attention to the possible risks that can affect their profitability. The impact of environmental, reputational and legal risks on the performance of manufacturing firms was examined in this paper. An exploratory research design was used by the researcher. The population of this study is 305 senior staff from 10 manufacturing companies in Lagos state's Ikorodu Metropolis. The Logit Binary regression model was used to test the study's hypotheses. This model is thought to be suitable because it can predict the impact of independent variables on dependent variables. According to the findings of this study, environmental risk, reputational risk, and legal risk all have a negative significant impact on the performance of manufacturing firms. This study recommended that manufacturing company management give greater attention to their environmental, reputational, and legal risks by making sure that such risks are properly managed with the help of Enterprise Risk Management Tools and by offering valuable intelligence into their entire organization with Data-Driven Decision Making. Manufacturing firms should use Optimised Heat Maps and Charts to distinguish, analyze, and assess Environmental Risk, Reputational Risk, and Legal Risk in order to avoid or minimize such risks.